(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
This study examines the application of the learning by drawing strategy as an innovative, student-centered approach to teaching Javanese script in elementary schools. Conducted at SDN Sepuh Gembol I, East Java, the research used a qualitative descriptive method involving third-grade students. Data were obtained through observation, interviews, and documentation of students’ drawing-based work. The findings show that early in the process, students exhibited low engagement, hesitation, and limited confidence in writing Javanese script. After drawing activities were integrated, students showed clear improvements in emotional involvement, enthusiasm, and participation. The study recorded a 25% increase in attention to explanations, a 40% rise in enthusiasm, a 45% increase in willingness to express opinions, and a 35% improvement in punctuality when submitting assignments. Through drawing, students creatively interpreted and personalized the script, strengthening both cognitive understanding and emotional connection. This approach also supported cultural appreciation by allowing students to engage with local heritage in a meaningful way. Overall, the study concludes that learning by drawing enhances academic outcomes while fostering cultural values, making it a relevant pedagogical model for modern education rooted in local wisdom